The application of numerical modeling to geothermal investments - Wachowicz-Pyzik, Anna; Pająk, Leszek; Papiernik, Bartosz; Michna, Michał (Computer Assisted Methods in Engineering and Science; Vol 22 No 4 (2015), 2017)
Among numerous applications of numerical modeling in many different fields of science, there is numerical modeling applied to the issues related to geothermal investments [1]. A number of important parameters and properties can be estimated based on numerical modeling. In the case of geothermal investments, we can determine several factors, which may influence operation of the heating plants, e.g.: exploitation and size of extraction and/or injection of groundwaters, selection of an optimal spacing of boreholes (in the case of geothermal doublets), and water temperature or pressure [2]. This paper presents the issues related to the numerical modeling of geothermal reservoirs as well as a variety of computer software packages commonly used in creation of static and dynamic models, such as: Visual MODFLOW, TOUGH, FEFLOWor Petrel [3, 4]. The process of numerical modeling is presented in four general steps: (1) archival data collection and analysis (often using statistical methods), (2) creation of the static and (3) dynamic numerical models of a reservoir, and (4) environmental, financial and technical assessments based on a mathematical model of surface installation [5]. Each step is presented in details and the most important reservoir parameters, which influence the utilization of geothermal energy, are discussed. At the end, the main directions in current utilization of geothermal waters in Poland and the future opportunities of geothermal heat generation, including the financial aspects related to geothermal investments, are discussed.